A spectacular effect of tocilizumab in Takayasu arteritis - Fatma Saïd; Ines Naceur; Tayssir Ben Achour; Mayssam Jridi; Monia Smiti (European Journal of Case Reports in Internal Medicine)
Background: Anti-interleukin-6 receptors (anti-IL-6R) have been a promising new therapeutic alternative in the treatment of Takayasu arteritis. Case description: We report the case of a 34-year-old patient with Takayasu arteritis diagnosed in 2017. While she was on corticosteroid and methotrexate, the patient presented twice with clinical and radiological signs of activity, requiring an increase of corticosteroid dose and an increase in the methotrexate dose to 20 mg/week. Anti-IL-6R infusions were indicated. At the end of the fifth infusion, the patient was totally asymptomatic: she no longer experienced episodes of syncope or amnesia. Conclusion: Our case perfectly illustrates the effectiveness of anti-IL-6R in the treatment of Takayasu arteritis, especially in its refractory form.